Conflict Management Strategies and Employee Performance in Mbale District Local Government - Isaac Sodo (Uganda Christian University, 2024)
This report has focused the impact of conflict management strategies and Mediation on Employee performance; effect of Negotiation on Employee performance and Effect of Arbitration on employee performance in local government in Mbale district. The study used Krejcie and Morgan (1970) table where 80 sample size of respondents selected from 100 of the employees of Mbale District Local Government of which only 78 respondents filled and returned the questionnaires.. The study used a cross section survey research design with both qualitative and quantitative approaches. The study population involved the Chief Administrative Officer, Heads of Departments, Principle personnel officer, Town clerks, sub-county chiefs and community development officers. Data collection utilized questionnaires and interviews. Data was analysed to obtain frequencies, mean, standard deviation, correlations and regression statistics to ascertain the significance of the variables. The realized that mediation slightly influences employee performance (r=.254, p=.043). Respondents revealed that mediation can only influence employee performance if it is done well. It was revealed that Arbitration has a significant influence on employee performance (r=.649, p=.000). Respondents appreciated that whenever arbitration is applied in managing conflicts, employees’ performance is improved. In addition, it was discovered that Negotiation influences employee performance (r=.555, p=.000). Respondents revealed that whenever there is a conflict, the parties in dispute are given an opportunity to meet, discuss and agree amicably. Respondents believe that after negotiation, there is improved employee relations that stimulates employee’s productivity. n conclusion, Conflict management strategies positively influences employee performance in Mbale District Local Government. It was therefore recommended that Arbitration committees should maintain high level of integrity, transparency and impartiality, negotiation should also be applied in other situations even if there is no conflict and Mediation can be used only in situations of low productivity, delay in accomplishment of tasks and absenteeism of employees at work.